PERBEDAAN BPR KECIL DAN MENENGAH, DITINJAU DARI EFISIENSI - I Gede Mandra; I Dewa Gede Bisma; Siti Nurmayanti; G.A. Sri Oktaryani (Jurnal Riset Akuntansi, 2019)
This study aims to test the small and medium-sized Credit Society Bank (CSB) in West nusa tenggara in by efficiency indicator. The type of research used comparative in difference small medium-sized efficiency CSB. Data obtain is financial report of all CSB in West Nusa Tenggara by documentation. With this different test, analysis by test mann-whitney can analyze without normality test. This non parametric test shows that there is no difference between CSB small and CSB medium in terms of their efficiency. It described the conditions CSB small and CSB medium having a similliarity operational activities in terms of operational costs and operating income.